Taxonomic contribution to the genus Zodarion Walckenaer, 1826 in Turkey with description of a new species (Araneae: Zodariidae) - Dimitrov, Dragomir (Zootaxa, 2020)
A new species of the genus Zodarion Walckenaer, 1826, Zodarion imroz spec. nov. is described based on a male from Gökçeada Island, Turkey. A new synonymy is established: Zodarion tireboluensis Danışman & Rubio, 2017 n. syn. = Zodarion abantense Wunderlich, 1980. New taxonomic images of the type specimens (male and female) of Z. abantense are given. Its distribution is summarized and discussed.